Prevalence and Influencing Factors of Obesity in Elementary School Children - Soepardi Soedibjo; Mulyadi M Djer; Agus Firmansyah (Indonesian Pediatric Society, 1998)
An observational, cross sectional study was conducted on elementary school students in Central Jakarta between May and October 1997. This preliminary study aimed to determine the prevalence and influencing factors of obesity in elementary school students. From 488 students studied, 47 were obese. The prevalence rate in this study was 9.6%, with boys twice as much as girls. Factors that influenced the incidence of obesity were: (1) age, (2) time of introduction of solid food during infancy, (3) eating habit, (4) calorie intake, and (5) physical activities. There were two factors that increased the incidence of obesity namely: (1) obesity of parents, and (2) birth weight. Environmental factors that increased the incidence of obesity were: (1) parent's occupation and (2) family income. Laboratory findings associated with obesity were: (1) increase blood cholesterol concentration, (2) increase blood triglyceride concentration, (3) decreased HDL cholesterol concentration, and (4) increased LDL cholesterol concentration. We conclude that the prevalence rate of obesity obtained in this study was higher compared with the previous studies, and that obesity in school children is influenced by many factors.